2013
DOI: 10.17722/ijme.v1i3.16
|View full text |Cite
|
Sign up to set email alerts
|

Market Efficiency and Volatility Spill over in Spot & Futures Currency Market

Abstract: The present study has analysed the long term relationship between spot and future prices of currency (dollar) for the period of study between 01/06/2009 and 10/07/2013. The spot and future prices of the currency is found to have long term relationship which is supported by the existence of an error correction mechanism called arbitrage. The error correction mechanism restores the equilibrium relationship whenever disequilibrium takes place between the two markets. It is the spot price which corrects the disequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Studies such as Wahab and Lashgari (1993), Chan and Lien (2001), Kumar and Chaturvedula (2007), Kumar and Tse (2009), Sriram and Senthil (2013), Zakaria (2012), Sehgal et al (2015), Boney et al (2018) have found the Spot Market playing a dominant role in the Price-Discovery process. In India, (Thenmozhi, 2002) and (Raju and Karande, 2003) analyzed the Lead-Lag and Price-Discovery of Equity Futures Market in India.…”
Section: Chanmentioning
confidence: 99%
“…Studies such as Wahab and Lashgari (1993), Chan and Lien (2001), Kumar and Chaturvedula (2007), Kumar and Tse (2009), Sriram and Senthil (2013), Zakaria (2012), Sehgal et al (2015), Boney et al (2018) have found the Spot Market playing a dominant role in the Price-Discovery process. In India, (Thenmozhi, 2002) and (Raju and Karande, 2003) analyzed the Lead-Lag and Price-Discovery of Equity Futures Market in India.…”
Section: Chanmentioning
confidence: 99%
“…They concluded that spot market play dominant role in price discovery process than futures market. Sriram and Senthil (2013) explored price discovery and volatility spillover in spot and futures currency market by the use of co-integration, GARCH and ECMs. They used daily spot and futures prices of USD/INR from 1 June 2009 to 10 July 2013.…”
Section: Review Of Literaturementioning
confidence: 99%